Role of Inner Ear Macrophages and Autoimmune/Autoinflammatory Mechanisms in the Pathophysiology of Inner Ear Disease - Miwa, Toru; Okano, Takayuki (Frontiers in Neurology, 2022)
Macrophages play important roles in tissue homeostasis and inflammation. Recent studies have revealed that macrophages are dispersed in the inner ear and may play essential roles in eliciting an immune response. Autoinflammatory diseases comprise a family of immune-mediated diseases, some of which involve sensorineural hearing loss, indicating that similar mechanisms may underlie the pathogenesis of immune-mediated hearing loss. Autoimmune inner ear disease (AIED) is an idiopathic disorder characterized by unexpected hearing loss. Tissue macrophages in the inner ear represent a potential target for modulation of the local immune response in patients with AIED/autoinflammatory diseases. In this review, we describe the relationship between cochlear macrophages and the pathophysiology of AIED/autoinflammatory disease.